Synthesis of α, β-unsaturated epoxy ketones utilizing a bifunctional sulfonium/phosphonium ylide. Issue 58 (28th June 2021) - Eskandari, Roozbeh; Hess, Jeremy P.; Tochtrop, Gregory P.
Abstract : Unsymmetric α, β-unsaturated epoxy ketones were synthesized from a bifunctional sulfonium/phosphonium ylide. Abstract : Herein, a new protocol for rapid synthesis of α, β-unsaturated epoxy ketones utilizing a bifunctional sulfonium/phosphonium ylide is described. This approach comprises two sequential chemoselective reactions between sulfonium and phosphonium ylides and two distinct aldehydes, which allows for the rapid construction of a variety of unsymmetric α, β-unsaturated epoxy ketones. This methodology allows the rapid construction of the core reactive functionality of a family of lipid peroxidation products, the epoxyketooctadecenoic acids, but can be further broadly utilized as a useful synthon for the synthesis of natural products, particularly those derived from oxidized fatty acids. Accordingly, a protocol utilizing this approach to synthesize the epoxyketooctadecenoic acid family of molecules is described.